Perbedaan persepsi terhadap karakteristikinovasi pada sekolah lapang pengelolaan tanaman terpadu padi sawah antar komunitas petani di Lampung - Slameto, Slameto (2014)
Improving production of rice national program in indonesia was lauched to fulfill the food of the comunity. It was made by increase rice productivity through the implementation of integrated crop management (ICM) of padies.The deployment acceleration by farmers field school (FSS) approach.The rate of adoption still tends slow . It was suspected because of the perception characteristic of innovations different inter ethnic farmers. The reseach was conducted to describe and analyze the difference of the perception charateristic of innovation ICM of paddies by farmers from Lampung ethnic, Jawa ethnic, and Bali ethnic .The research methods with survey on FFS-ICM of paddies participant. The sample total 286 farmers.The research carried out Juni-Septemer 2013. The located in Lampung Tengah, Lampung Selatan dan Lampung Barat regency. The data analysis done with the different variance. The result indicate that, the perception characteristic of innovation ICM of learning FFS between Lampung-Java-Bali ethnic shows that the obvious difference. It was can be taken consideration to increasing the effectiveness of the learning FFS-ICM of paddies and to accelerate the deployment and adoption of innovation ICM paddies